THE STUDY OF CULTURAL SEMIOTICS: SANGJIT CEREMONY IN BANGKA BELITUNG - Simamora, Riris Mutiara; Shi, Neo Ke (Balai Bahasa Sumatra Barat, 2022)
Sangjit is a one of the ceremony series that Tionghoa ethnic do before wedding process. This tradition is hereditary since the past up to these recent days. Chine ethnic has many steps before they do the wedding ceremony, one of them is sangjit. This analysis is using the theory from Danesi and Perron (1999) about cultural marks, known as three-dimensional analysis which includes temporal, notational, and structural analysis. The data in this research use primary data as the data source with descriptive-qualitative method. The researchers take the object from photos of Sangjit Wedding Ceremony in Bangka Belitung which taken directly. The result of this research is found that annotative in the notational dimension, analogical in structural dimension and dynamic in the temporal dimension. Keywords: Sanjit ceremony, Semiotics, Tionghoa, Bangka-Belitung